PEMODELAN MATEMATIKA PADA KASUS INFEKSI COVID-19 - Debora Exaudi Sirait; Erwin Sirait; Imelda Sirait (Universitas Islam Sumatera Utara, 2023)
One of the viruses that cause infectious diseases is the corona virus. Corona viruses can cause more serious diseases such as the Severe Acute Respiratory Syndrome-Corona Virus which was epidemic in 2003, the Middle East Respiratory Syndrome-Corona Virus outbreak in 2012 and the 2019 Coronavirus Disease which was epidemic at the end of 2019. The ordinary linear differential equation is an equation differential in which all derivatives appear in linear form and no coefficients depend on the dependent variable. The coefficient can be a function of the independent variable, in which case the differential equation is a linear differential equation with changing coefficients. Based on the relatively large number of cells that are susceptible to infection (S), over time it will decrease and towards a zero value against high immunity, and people under surveillance and patients in care (E) with time will decrease towards high immunity. Meanwhile, the number of infected cells (I) at one time will reach a highest point, which indicates the maximum number of infected cells and gradually decreases with time towards a high increase in immunity. Because fewer S, E, and I are infected, the amount of virus in the body (R) also decreases.